The Effect of Job Satisfaction and Organizational Commitment on Employee Performance: A Narrative Literature Review - Indah Anggraeni Purnama Sari; Masduki Asbari; Nelson Silitonga; Yunianto Agung Nugroho; Jaka Suwita; Muhammad Johan; Akhmad Farhan (Motivaksi: Jurnal Ilmu Sosial, Manajemen, Akuntansi dan Bisnis, 2026)
This research aims to analyze the influence of job satisfaction and organizational commitment on employee performance through observation of narrative literature. The method used is a literature study of three relevant national journal articles sourced from Google Scholar. The research results show that job satisfaction and organizational commitment have a positive and significant effect on employee performance, both partially and simultaneously. Employees who feel satisfied and have high commitment to the organization tend to show more optimal performance. These findings emphasize the importance of job satisfaction and organizational commitment in improving employee performance in various organizational sectors.     Keywords: Job Satisfaction; Organizational Commitment; Employee Performance; Literature Review